Signaling, Investment Opportunities, and Dividend Announcements - Yoon, Pyung Sig; Starks, Laura T. (Review of Financial Studies, 1995)
This article examines potential explanations for the wealth effects surrounding dividend change announcements. We find that new information concerning managers' investment policies is not revealed at the time of the dividend announcement. We also find that dividend increases (decreases) are associated with subsequent significant increases (decreases) in capital expenditures over the three years following the dividend change, and that dividend change announcements are associated with revisions in analysts' forecasts of current earnings. These results are consistent with the cash flow signaling hypothesis rather than the free cash flow hypothesis as an explanation for the observed stock price reactions to dividend change announcements.